Molecular- and nano-tubes - Hayden, Oliver; Nielsch, Kornelius; SpringerLink (Online service). (New York Springer, 2011)
Molecular- and Nano-Tubes summarizes recent advancements in the synthesis, fabrication and applications of tubular structures.  An interdisciplinary overview of innovative science  focused on tubular structures is provided.  The reader is offered an overview of the different fields that molecular and nano tubes appear in, in order to learn the fundamental basics as well as the applications of these materials. This book also:  Shows how nanotechnology creates novel materials by crossing the barriers between biology and material science, electronics and optics, medicine and more Demonstrates that tubes are a fundamental element in nature and used in disparate applications such as ion channels and carbon nanotubes  Molecular- and Nano-Tubes is an ideal volume for researchers and engineers working in materials science and nanotechnology.
Foreword -- Introduction -- Molecular Scale Tubes -- Supramolecular Tubes -- Carbon Nanotubes -- Inorganic Nanotubes.
Electronic reproduction.
Keywords: Nanotubes; Electronic books